2006
DOI: 10.1152/ajplung.00180.2005
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar fluid reabsorption is increased in rats with compensated heart failure

Abstract: ) is important in keeping the air spaces free of edema. This process is accomplished via active transport of Na ϩ across the alveolo-capillary barrier mostly by apical Na ϩ channels and basolateral Na ϩ -K ϩ -ATPases. Recently, we have reported that acute elevation of left atrial pressures is associated with decreased AFR in isolated rat lungs. However, the effect of chronic elevation of pulmonary capillary pressure, such as seen in patients with congestive heart failure (CHF), on AFR is unknown. CHF was induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…This result supports previous animal investigations in isolated perfused lungs from volume overload CHF [12,13], as well as the trend observed in a decompensated patient population [14], in which there is an increase in alveolar fluid clearance, but is inconsistent with our previous findings in the isolated nonperfused rat lung [8].…”
Section: Accepted M Manuscriptsupporting
confidence: 64%
See 2 more Smart Citations
“…This result supports previous animal investigations in isolated perfused lungs from volume overload CHF [12,13], as well as the trend observed in a decompensated patient population [14], in which there is an increase in alveolar fluid clearance, but is inconsistent with our previous findings in the isolated nonperfused rat lung [8].…”
Section: Accepted M Manuscriptsupporting
confidence: 64%
“…It has been suggested that increased rate of alveolar fluid clearance in CHF may be due to an increase in the absolute expression and activation of vectorial fluid channels on both endothelial and epithelial cells, controlled through a nitric oxide negative feedback mechanism [12,13]. This mechanism, which allows for an increase in fluid flux capacity of the lung in CHF, provides a possible explanation for our previous finding of…”
Section: Accepted M Manuscriptmentioning
confidence: 54%
See 1 more Smart Citation
“…With respect to the former, Campbell and colleagues (8) found that instilled ␤ 2 -agonists failed to stimulate alveolar fluid clearance in sheep in which left atrial pressure had been increased for 4 h. Consistent results were observed in ex vivo isolated, perfused rat lungs (41), where lung fluid absorption was decreased following an hour elevation of left atrial pressure. In contrast, over a longer time frame of 7 days, Azzam and colleagues (3) observed that baseline alveolar fluid clearance was increased in rats with compensated heart failure produced by an aorto-caval fistula. These authors suggested that this response was mediated by an increased endogenous plasma norepinephrine upregulation of active Na transport.…”
Section: L490mentioning
confidence: 92%
“…1B and C respectively). We suggested that this upregulation of Na + transport is enhanced in order to keep the alveolar spaces free of edema in experimental chronic CHF [41].…”
Section: Alveolar Fluid Clearance In Chronic Left Heart Failurementioning
confidence: 94%